Perception and eating habits during the COVID-19 quarantine in Peru - Guillen-Sánchez, Jhoseline (2021)
A survey was conducted between May and June 2020 to 164 people from the department of La Libertad, Peru, with the objective of analyzing how the pandemic affected food consumption in the Peruvian population, and if new forms of eating habits can be unfavorable for adequate nutrition. 84.4 % of those surveyed are between 18 and 35 years old and 53.1 % were female. Technical higher education was the predominant level of instruction. The most frequent changes refer to higher consumption of fruits and vegetables (32 %), and reduction in the consumption of dairy products such as yogurt, milk and cheese (22 %). Medium priority food products, such as industrialized beverages and confectionery products, showed a reduction of 68%. After buying food, 45 % ofrespondents sanitize the products with disinfectants for domestic use. For 55 % of respondents, a healthy diet strengthens the immune system and reduces the propensity for coronavirus infection.